Growth rates of common tree species in Westminster, Colorado - Wood, Keith, author; Colorado State Forest Service, publisher (Colorado State University. Libraries, 2010)
This study updates a previous project and publication from 2000 in which tree-growth rates were analyzed on public property in Westminster, Colo. Eight years of diameter growth data were collected in 2000 and updated in early 2008 to obtain 16 years of growth data on the same trees. Growth rates for trees typically are classified based on individual observation or experience. This study, based on trees originally inventoried in late 1992 and early 1993, attempts to measure tree diameter growth rates to more accurately reflect what can be expected of trees growing in this area.
Keywords: Westminster; trees; growth rate; tree diameter; Colorado